IMPLEMENTASI MANAJEMEN MUTU DALAM PENINGKATAN KOMPETENSI PROFESIONAL GURU DI MTS AL AMIRIYYAH BLOKAGUNG BANYUWANGI - Moh. Harun Al Rosid; Erina Ramadhani Ayudin (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2021)
The purposes of this research are : (1) to find out the implementation of quality management in MTs Al Amiriyyah in the 2020/2021 academic year, (2) to find out how profwssional cpmpetence oh teacher at MTs Al Amiriyyah in the 2020/2021 academic year, (3) to find out effort what the school does in improving the professional competence of MTs Al Amiriyyah teacher for the 2020/2021 academic year. Data collection techniques used are observation, interviews and documentation. The data analysia used is data analysis by Milles and Huberman with the analysis steps, namely: (1) data reduction, (2) data presentation, (3) drawing conclusions. Meanwhile, the data validity test uses the credibility, auditibility, dependibility, and confirmability tests. The results of this study indicate that : (1) MTs Al Amiriyyah has implemented integrated quality management well, this can be seen through continuous reconciliation carried out by the head of the madrasa, including all component in deciding problems and making decisions according to facts, (2) professional competence teacher at MTs Al Amiriyyah owned by teacher are not evenly distributed, there are teacher who are professional and some have not been proven by educator certificates, (3) school principals have made efforts aimed at improving the professional competence of teachers at MTs Al Amiriyyah which includes monitoring activities, supervision, training, job placement, additional teaching hours and certification program.